Are "Theory of Mind" Skills in People with Epilepsy Related to How Stigmatised They Feel? An Exploratory Study. (18th August 2016) - Noble, A. J.; Robinson, A.; Marson, A. G.
Abstract : Feelings of stigma are one of the main burdens reported by people with epilepsy (PWE). Adults with temporal or frontal lobe epilepsy and children with idiopathic generalised epilepsy are at risk of Theory of Mind (ToM) deficits. ToM refers to social cognitive skills, including the ability to understand the thoughts, intentions, beliefs, and emotions of others. It has been proffered that ToM deficits may contribute to the feelings of stigma experienced by PWE. In this study we tested this for the first time. We also determined the association between clinical and demographic factors and ToM performance. Five hundred and three PWE were recruited via epilepsy organisations and completed measures online. Feelings of stigma were measured using Jacoby's Stigma Scale, whilst the Reading the Mind in the Eyes Test and the Faux Pas Test measured ToM. The median age of participants was 37 years, their median years living with epilepsy were 15, and 70% had experienced seizures in the prior 12 months. Feelings of stigma held a negligible, negative, and nonsignificant association with ToM performance (r s −0.02 and- 0.05 ). Our results indicate that the ToM model for understanding epilepsy stigma has limited utility and alternative approaches to understanding and addressing epilepsy-related stigma are required.